Possible Role of High Temperature and Soil Biological Fertility on Kiwifruit Early Decline Syndrome - Bardi, Laura; Nari, Luca; Morone, Chiara; Faga, Maria Giulia; Malusà, Eligio (Frontiers in Agronomy, 2020)
Kiwifruit early decline is a disorder widespread worldwide in kiwifruit orchards, worsened in the last few years, seriously affecting economic sustainability of several rural areas where kiwifruit is an important crop. The symptoms include leaf epinasty, chlorosis, desiccation and abscission, reduced fruit production, anomalous root morphology and anatomy, followed by the plant collapse and death, usually in the same or the following year after symptoms occurrence. Even though several phytopathological or agronomical studies have been carried out, a clear and univocal explanation of the causes and the possible remedies are yet to be understood. A field trial has been carried out in an experimental kiwifruit orchard, in which several soil management practices (ridging, amendment with compost, bioinoculation with selected rhizospheric microorganisms) were tested to evaluate their effect on early decline symptoms occurrence. The analysis of plant growth parameters, root morphology and anatomy, and symptoms onset were related to environmental data (air and soil temperature, soil water tension). The results pointed to a possible role and interaction between agronomic soil management and climatic conditions as the triggering factors of kiwifruit early decline syndrome.